The opinion of Turkish cardiologists on current malpractice system and an alternative patient compensation system proposal: PCS study group - Ayhan Olcay; Sadık Volkan Emren; Gamze Babür Güler; Ekrem Güler; Vedat Ertunç; Rida Berilgen; Abdullah Aslan; Ersin Çağrı Şimşek; Şükriye Ebru Gölcük; Kıvanç Yalın (KARE Publishing, 2017)
Objective: Cardiologists participate in the diagnosis and interventional treatment of numerous high-risk patients. The goal of this study was to investigate how the current malpractice system in Turkey influences cardiologists' diagnostic and interventional behavior and to obtain their opinions about an alternative patient compensation system. Methods: The present cross-sectional study assessed the practice of defensive medicine among cardiologists who are actively working in various types of workplace within the Turkish healthcare system. A 24-item questionnaire was distributed to cardiology residents, specialists, and academics in Turkey in print format, by electronic mail, or via cell phone message. Results: A total of 253 cardiologists responded to the survey. Among them, 29 (11.6%) had been sued for malpractice claims in the past. Of the cardiologists who had been sued, 2 (6.9%) had been ordered to pay financial compensation, and 1 (3.4%) was given a sentence of imprisonment due to negligence. In all, 132 (52.8%) of the surveyed cardiologists reported that they had changed their practices due to fear of litigation, and 232 (92.8%) reported that they would prefer the new proposed patient compensation system to the current malpractice system. Among the cardiologists surveyed, 78.8% indicated that malpractice fear had affected their decision-making with regard to requesting computed tomography angiography or thallium scintigraphy, 71.6% for coronary angiography, 20% for stent implantation, and 83.2% for avoiding treating high-risk patients. Conclusion: The results of this survey demonstrated that cardiologists may request unnecessary tests and perform unneeded interventions due to the fear of malpractice litigation fear. Many also avoid high-risk patients and interventions. The majority indicated that they would prefer the proposed alternative patient compensation system to the current malpractice system.